The association of phosphoinositide 3-kinase enhancer A with hepatic insulin receptor enhances its kinase activity - Chan, Chi Bun (Nature Publishing Group, 2011)
Dysfunction of hepatic insulin receptor tyrosine kinase (IRTK) causes the development of type 2 diabetes. However, the molecular mechanism regulating IRTK activity in the liver remains poorly understood. Here, we show that phosphoinositide 3-kinase enhancer A (PIKE-A) is a new insulin-dependent enhancer of hepatic IRTK. Liver-specific Pike-knockout (LPKO) mice display glucose intolerance with impaired hepatic insulin sensitivity. Specifically, insulin-provoked phosphoinositide 3-kinase/Akt signalling is diminished in the liver of LPKO mice, leading to the failure of insulin-suppressed gluconeogenesis and hyperglycaemia. Thus, hepatic PIKE-A has a key role in mediating insulin signal transduction and regulating glucose homeostasis in the liver.